1997
DOI: 10.1038/sj.onc.1201329
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of cell cycle control by vitamin D3 and its analogue, EB1089, in human breast cancer cells

Abstract: Examination of a panel of ER positive breast cancer cell lines showed that they were dierentially growth inhibited by vitamin D 3 and its analogue EB1089. EB1089 treatment of the breast cancer cell lines MCF-7 E, BT20, T47D, and ZR75 demonstrated a correlation between a reduction in Cdk2 kinase activity towards phosphorylation of histone H1 and a decrease in DNA synthesis, while no modulation of Cdk2 activity was observed in the vitamin D 3 and EB1089 resistant cell line MCF-7 L. This was accompanied by a time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
1
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 44 publications
2
69
1
3
Order By: Relevance
“…However, the mechanisms by which these compounds generate inhibition of proliferation and induction of apoptosis in tumor cells are not fully understood. The inhibition of cell proliferation mediated by VD3 compounds has been reported to be due to modulation of cell cycle regulators and a G1 phase arrest through induction of p21 and p27 in pancreatic and breast cancer cells (Kawa et al, 1997;Wu et al, 1997;Verlinden et al, 1998). However, another report showed that VD3-induced G1 arrest is associated with a significant decrease of p21 and increase of p27 in squamous cell carcinoma cells (Hershberger et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…However, the mechanisms by which these compounds generate inhibition of proliferation and induction of apoptosis in tumor cells are not fully understood. The inhibition of cell proliferation mediated by VD3 compounds has been reported to be due to modulation of cell cycle regulators and a G1 phase arrest through induction of p21 and p27 in pancreatic and breast cancer cells (Kawa et al, 1997;Wu et al, 1997;Verlinden et al, 1998). However, another report showed that VD3-induced G1 arrest is associated with a significant decrease of p21 and increase of p27 in squamous cell carcinoma cells (Hershberger et al, 1999).…”
Section: Introductionmentioning
confidence: 97%
“…Increases in p21 expression at the mRNA and protein level have been documented in association with G1 arrest mediated by 1,25(OH) 2 D 3 or certain of its synthetic analogues (James et al 1996, Mørk Hansen et al 2001b. A study in MCF-7 breast cancer cells treated with the vitamin D analogue EB1089 demonstrated a correlation between increased p21 WAF-1/CIP1 protein levels, inhibition of Cdk2-associated histone H1 kinase activity and G1 arrest (Wu et al 1997). Effects of 1,25(OH) 2 D 3 on p27 kip1 appear to vary with cell type.…”
Section: Mechanisms Associated With Inhibitory Effects Of Vitamin D Cmentioning
confidence: 99%
“…Treatment of oestrogen receptor-positive MCF-7 breast cancer cells with 1,25(OH) 2 D 3 induces cell cycle arrest in G0/G1 (Simboli-Campbell et al 1997, Wu et al 1997. These effects are accompanied by alterations in the expression of important cell cycle regulators such as increases in cyclin-dependent kinase (cdk) inhibitors and dephosphorylation of the retinoblastoma protein (Fan & Yu 1995, Mørk Hansen et al 2001b.…”
Section: Mechanisms Associated With Inhibitory Effects Of Vitamin D Cmentioning
confidence: 99%
“…1,25-D3 is responsible for VDR-mediated apoptosis and inhibits angiogenesis and differentiation in a variety of cancer types (13,(16)(17)(18)(19)(20). 1,25-D3 is a potential antitumor agent because of its ability to regulate cancer cell growth.…”
mentioning
confidence: 99%
“…1,25-D3 is well known for its antiproliferative roles including the induction of G 0 -G 1 cell-cycle arrest with associated down-regulation of oncogenic cyclins D1 and D3 and p27/p21 induction (12)(13)(14)(15). 1,25-D3 is responsible for VDR-mediated apoptosis and inhibits angiogenesis and differentiation in a variety of cancer types (13,(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%